All Days 2011
DOI: 10.2118/144313-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Research on Optimizing the Plan of New Unary Polymer Surfactant Improving the Effect of Development in Thick Oil Pay

Abstract: Polymer surfactant is a unitary flooding system which be developed in recent years. It has dual characteristics of polymer and surfactant. It has strong solvency even at a lower concentration. It has low molecular weight, counter-mass, high viscosity, anti-shearing force, anti-biodegradation, anti-oxidation degradation, temperature-resistance and salt resistance, and it fits different permeability reservoir. It is also be used to under different mineral degree condition reservoir and be injected with waste wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Global warming and insufficient energy supply have aroused interest in enhanced oil recovery (EOR) with CO 2 and CO 2 capture, utilization and storage (CCUS). Injection of CO 2 into oil reservoirs known as CO 2 -enhanced oil recovery (EOR) can not only help to store the CO 2 but also improve the recovery of crude oil. Hence, this process is considered to be the most cost-effective CCUS technique and has been widely used in the development of oilfields. , In CO 2 injection EOR projects, CO 2 diffuses into the formation and helps improve oil recovery by reducing the crude oil viscosity, supplementing the formation energy, swelling oil volume, and reducing the interfacial tension. , Studies have shown that the in situ mass transfer between CO 2 and heavy oil under reservoir conditions is dominated by molecular diffusion and dispersion. , The magnitude of molecular-diffusion coefficients affects the time for the heavy oil to achieve desirable viscosity reduction and swelling effect, thus influencing the oil-production response. , Therefore, the determination of CO 2 diffusion coefficient has extremely important guidance on CO 2 -EOR risk assessment, engineering design, and economic evaluation. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global warming and insufficient energy supply have aroused interest in enhanced oil recovery (EOR) with CO 2 and CO 2 capture, utilization and storage (CCUS). Injection of CO 2 into oil reservoirs known as CO 2 -enhanced oil recovery (EOR) can not only help to store the CO 2 but also improve the recovery of crude oil. Hence, this process is considered to be the most cost-effective CCUS technique and has been widely used in the development of oilfields. , In CO 2 injection EOR projects, CO 2 diffuses into the formation and helps improve oil recovery by reducing the crude oil viscosity, supplementing the formation energy, swelling oil volume, and reducing the interfacial tension. , Studies have shown that the in situ mass transfer between CO 2 and heavy oil under reservoir conditions is dominated by molecular diffusion and dispersion. , The magnitude of molecular-diffusion coefficients affects the time for the heavy oil to achieve desirable viscosity reduction and swelling effect, thus influencing the oil-production response. , Therefore, the determination of CO 2 diffusion coefficient has extremely important guidance on CO 2 -EOR risk assessment, engineering design, and economic evaluation. , …”
Section: Introductionmentioning
confidence: 99%
“…9,10 In CO 2 injection EOR projects, CO 2 diffuses into the formation and helps improve oil recovery by reducing the crude oil viscosity, supplementing the formation energy, swelling oil volume, and reducing the interfacial tension. 11,12 Studies have shown that the in situ mass transfer between CO 2 and heavy oil under reservoir conditions is dominated by molecular diffusion and dispersion. 13,14 The magnitude of molecular-diffusion coefficients affects the time for the heavy oil to achieve desirable viscosity reduction and swelling effect, thus influencing the oil-production response.…”
Section: Introductionmentioning
confidence: 99%